COAL STOCKS: UNDERVALUED OR OVERHYPED VALUATION STUDY WITH EV/EBITDA: (Study On Coal Commodity Stock Group For The Period 2020-2024) - Sudiarto, Edi; Pudjiastuti, Widanarni (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study evaluates the stock valuation of ITMG, BYAN, and PTBA using the EV/EBITDA method during the period 2020–2024 to determine whether the stocks are undervalued or overvalued . The data used comes from the company's financial statements and related publications. The analysis was carried out by comparing the EV/EBITDA value of each company to the industry average each year. The results of the study show that ITMG is consistently undervalued , with a lower EV/EBITDA ratio than the industry average. BYAN , on the other hand, tends to be overvalued , especially in the last three years with a ratio that is much higher than the industry average. PTBA experienced a change in trend, from being overvalued in 2020–2021 to being undervalued from 2022 to 2024. These results indicate that undervalued stocks such as ITMG and PTBA can be an investment opportunity for investors seeking attractive valuations, while BYAN's overvalued shares require further analysis related to market expectations and company growth. This study provides insight for investors in optimizing investment decisions in the coal sector.